PENGARUH PROFESIONALISME KERJA APARATUR TERHADAP KUALITAS PELAYANAN PUBLIK DI DINAS PENDIDIKAN KABUPATEN KETAPANG - Martha Magda Lena Sinaga E.42009022 (FISIP Universitas Tanjungpura Pontianak, 2013)
This thesis was aimed to find out how much the apparatus’ professionalism influenced the quality ofpublic service of Education Department in Ketapang Regency. This research was carried out basedon the problems which were related to the service quality given by the apparatus’ of the EducationDepartment, and the apparatus’ professionalism was one of the factors which influence the servicequality. This research was carried out by using quantitative paradigm with associative method/causal relation. The hypotheses in this research were Ho : There is no significant influence betweenthe employees’ professionalism and the quality of public service of Education Department inKetapang Regency, and Ha : There is a significant influence between the employees’professionalism and the quality of public service of Education Department in Ketapang Regency.The samples of this research were the school teachers as the recipients of the service from EducationDepartment in Ketapang Regency. The result of the calculation which used product momentcorrelation with significant level (a) 5% was that the influence of the employees’ professionalism onthe quality of public service was 0,567. The result of coefficient determination calculation was thatthe influence of the employees’ professionalism on the quality of public service of EducationDepartment in Ketapang Regency was 32,14%, whereas 67,86% was influenced by other factorswhich were not discussed in this research. Key Words : Professionalism, Public Service, Education